Salinity Fluctuation on the Genetic Regulatory Mechanisms of the Crustacean, Charybdis japonica - Shui, Bonian; Wang, Yuju; Lou, Fangrui; Han, Zhiqiang (Frontiers in Marine Science, 2022)
The intertidal salinity fluctuations provide pose a significant physical challenge for the crustaceans that live here. In the present study, Charybdis japonica was selected as the research species to explore the genetic regulatory mechanisms of intertidal crustaceans responding to salinity fluctuations. We cultured C. japonica s with three salinity gradients (the salinity of 15‰, 25‰, and 35‰) and 68.90 Gb clean transcriptome reads were obtained by RNA-seq. All clean reads were then de novo assembled to 41,058 unigene with a mean length of 1,179.39 bp and an N50 length of 2,033 bp. Furthermore, a total of 18,100 (24.74%) unigenes were successfully matched with the sequences from at least one database. We further analyzed the transcriptome structure of C. japonica and a total of 26,853 CDSs and 12,190 SSRs were predicted. The gene expression levels of C. japonica at 25‰ were used as control, and 204 and 5,392 DEGs were found at the salinity of 35‰ and 15‰, respectively. Based on the annotated information of DEGs, we speculated that C. japonicas were subjected to greater stress under the salinity of 35‰ and isotonic intracellular regulation was activated. Furthermore, neuronal activity, oxidation response, intracellular regulatory activity and osmotic regulation-related genes were speculated to be critical genes for C. japonica to cope with salinity fluctuations. The present results will provide fundamental information for revealing the salinity fluctuation-related genetic regulatory mechanisms of C. japonica and other intertidal crustaceans, and then help us predict how future salinity changes will affect the survival of crustaceans.